Infundibulum aortic calcification in ductus arteriosus - Domínguez, Pedro (1960)
There have been 4 cases of patent ductus arteriosus in which calcification of the ductus region on the image plate was observed. The radiographic image feature corresponds to a calcium deposit in the aortic walls next to the aortic opening of the ductus . This area has been identified as the aortic infundibulum . In a review of published cases of patent ductus arteriosus with calcifications recognized at autopsy or x-rays, it was observed that the age of the patients was distributed from 29 to 79. Calcification occurred in cases with and without pulmonary hypertension, although the former were in the majority. The finding of calcification feature helps in the diagnosis of patent ductus arteriosus with pulmonary hypertension , especially in the differential diagnosis between patent ductus with reversed shunt and large VSD with left to right shunt ( Eisenmanger complex ) , whose manifestations clinics are very similar. Calcification appear as a result of increased flow and level infundíbulim aortic orifice of the ductus . Calcification does not contraindicate operation, if this is deemed necessary .